HRM Practices and Its Impact on Employee Satisfaction - et. al., Dr. Pallavi Badre, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Companies that perform well with respect to sustainability have a clear strategy which guides their sustainability activities. The relationship between sustainability and business strategy is clearly expressed. Human resource management plays a critical role in supporting the organizations to improve effectiveness, to manage corporate governance and ethical issues beyond economic performance. In Human resource management, sustainability is used, to refer to human resources, which foster a conducive working environment and positive human and social outcomes without focusing on financial strategies and results. The current study focuses on the study of impact of HRM practices on employee satisfaction. This study conducted with 100 employees from manufacturing sectors in Nagpur Maharashtra. HRM practices such as Training and Development, Performance Appraisal, Compensation and benefits practices as well as reward and recognition practices. Descriptive analysis was conducted with help of statistical tools correlation and Regression analysis. Results shows that HRM practices like compensation, performance appraisal and rewards and recognition have greater impact on employee satisfaction while training and development practices has lower effect on employee satisfaction.